Prevalence and associated factors of gestational diabetes mellitus in a high complexity hospital (Research, Society and Development, 2020)
Objective: to estimate the prevalence and associated risk factors of gestational diabetes mellitus (GDM) in a highly complex hospital service. Methodology: this is an observational, analytical, retrospective and cohort study carried out in a highly complex hospital service for pregnant women. Data from 421 pregnant women were included in the study. GDM classification was conducted according to the International Diabetes Association and Pregnancy Study Group (IADPSG) criteria. Results: the prevalence of GDM was 18.5%. As for the risk factors, participants who had alterations in their fasting blood glucose tests were 16% more likely to have GDM. Moreover, alterations in the oral glucose tolerance test (OGTT 1h) indicated 6% more chances of GDM in comparison to women without altered OGTT 1h test results. Conclusion: GDM is a highly prevalent disorder associated with negative outcomes for mothers and babies, considered a public health issue. Adequate, early management might result in satisfactory results for both pregnant women and their children.